Part III Indigenous Peoples and the Canadian Constitution, B Treaties, Ch.14 Treaties as Constitutional Agreements - Grammond, Sébastien (The Oxford Handbook of the Canadian Constitution, 2017)
This chapter reviews the history of treaty-making with the Indigenous peoples of Canada. After an initial period of roughly equal relationships, colonial authorities increasingly used treaties as a domestic law concept aimed at securing control over Indigenous land. The practice was continued after Confederation, but there appears to be a major misunderstanding as to the terms of those treaties, in particular as to the purported extinguishment of Aboriginal title. After a 50-year hiatus, treaty-making resumed in 1975 with the signing of ‘land claims agreements’ in most of the Canadian north. These agreements not only provide for the sharing of land, they also contain detailed provisions with respect to co-management of natural resources and, in some cases, self-government. Canadian law now affords statutory and constitutional protection to treaty rights, and courts are prepared to take into account extrinsic and oral evidence in interpreting treaties.